Biosorption of Cd(II) and Co(II) Ions‏ ‏from ‎Contaminated Water‏ ‏onto Cyanophyta: Single ‎And Binary Ion Exchange Isotherm (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study used both single and binary biosorption of Cd(II) and Co(II) ions from a synthetic contaminated water onto a dead blue-green (Cyanophyta) algae \ as biosorbent of heavy metals. Experimental parameters included pH, initial metal concentrations, agitation speeds, contact time and temperatures were investigated. The uptake capacities were 38.4 and 23.5 mg/g for Cd (II) and Co(II), respectively. The best pH values were 5 for Co (II) and Cd (II), respectively, and the contact time was1. 5 hr. A sequence of batch experiments was performed in a batch device in order to get equilibrium isotherm data of single and binary metals solutions for biosorption. The ion exchange mechanism was the base absorption of these metals, along with the light metal release like sodium, magnesium, calcium and potassium therefore a model ion exchange had been found appropriate to describe the process of biosorption. However, the calculated affinity constant (K) sequence for both single and binary system was 2.33, 5.43 respectively, for Cd (II) and 1.87, 2.46 for Co (II) with less than 5% percentage error; these values remain in both systems that the Cd(II) was the strongest one. The affinity constant in the single and binary system was KCd > KCo